Viral infections in renal transplant recipients. - Armstrong, J A (1976)
Cytomegalovirus (CMV) infections are common in renal transplant recipients. We studied 23 recipients prospectively to determine whether infections by other herpes-group and non-herpes-group viruses were also present. Sera, obtained at the time of surgery and periodically thereafter, were tested for antibody to CMV, herpes simplex virus (HSV), Epstein-Barr virus (EBV), parainfluenza viruses types 1, 2, and 3, and the viruses of measles and rubella. We found no evidence of an unusual incidence of primary or secondary infection by the non-herpesviruses tested. Rises to CMV, HSV, and EBV antibody titers occurred in 43, 38, and 32% of patients, respectively. All serological rises to herpes-group viruses occurred in patients seropositive at the time of transplantation, with the exception of three patients who experienced primary CMV infections. We conclude that reactivation of all herpes-group viruses tested may occur in transplant recipients. Morbidity was associated only with primarly CMV infection.